Minimizing bleeding and transfusion in single-stage bilateral hip and knee arthroplasty: A systematic review of current interventions - R. Gonzalez-Pola; R.O. Tafoya-Olivos; L.A. Culebras-Almeida; G. Zermeño-Garcia; A. Herrera-Lozano (Revista Española de Cirugía Ortopédica y Traumatología)
Objectives: To evaluate perioperative strategies for minimizing bleeding and transfusion needs in single-stage bilateral hip and knee arthroplasty. This systematic review identifies effective interventions and provides evidence-based recommendations and highlight areas for future research in optimizing bleeding management. Methods: A systematic review of literature from January 2010 to October 2024 was conducted, focusing on randomized controlled trials (RCTs), meta-analyses, and guidelines. Databases searched included PubMed/MEDLINE, Embase, Cochrane Library, and Web of Science. Interventions assessed included tranexamic acid (TXA), surgical techniques, regional anesthesia, controlled hypotension, preoperative anemia correction, tourniquet use, bone wax, and restrictive transfusion strategies. Study selection, data extraction, and quality assessment followed PRISMA and Newcastle-Ottawa Scale guidelines. Results: From 325 included studies, TXA consistently demonstrated the most significant impact, reducing transfusion rates by 40–60%. Anterior THA was associated with reduced blood loss. Regional anesthesia and controlled hypotension further minimized intraoperative bleeding. Preoperative anemia correction and restrictive transfusion thresholds also showed benefits. Tourniquet evidence was inconclusive. Limited evidence supported bone wax. GRADE assessment suggested high evidence quality for TXA and regional anesthesia, moderate for minimally invasive surgery, anemia correction, and restrictive transfusion, and low for bone wax. Conclusions: Multimodal approach integrating TXA, regional anesthesia, minimally invasive surgery, anemia correction, and restrictive transfusion protocols effectively reduces bleeding and transfusion needs in bilateral arthroplasty. Incorporation into Enhance recovery after surgery (ERAS) protocols is recommended. Future research should refine TXA dosing, clarify tourniquet use, and assess cost-effectiveness. Resumen: Objetivos: Evaluar estrategias perioperatorias para minimizar el sangrado y la necesidad de transfusiones en la artroplastia bilateral simultánea de cadera y rodilla. Esta revisión sistemática identifica intervenciones efectivas, proporciona recomendaciones basadas en la evidencia y destaca áreas para futuras investigaciones en la optimización del manejo del sangrado. Métodos: Se realizó una revisión sistemática de la literatura publicada desde enero de 2010 hasta octubre de 2024, centrada en ensayos clínicos aleatorizados (ECA), metaanálisis y guías clínicas. Las bases de datos consultadas fueron PubMed/MEDLINE, Embase, Cochrane Library y Web of Science. Las intervenciones evaluadas incluyeron ácido tranexámico (TXA), técnicas quirúrgicas, anestesia regional, hipotensión controlada, corrección preoperatoria de anemia, uso de torniquete, cera ósea y estrategias restrictivas de transfusión. La selección de estudios, la extracción de datos y la evaluación de la calidad se realizaron siguiendo las guías PRISMA y la escala Newcastle-Ottawa. Resultados: De los 325 estudios incluidos, el TXA mostró consistentemente el mayor impacto, reduciendo las tasas de transfusión entre un 40 y un 60%. La artroplastia total de cadera por abordaje anterior se asoció con una reducción en la pérdida sanguínea. La anestesia regional y la hipotensión controlada también minimizaron significativamente el sangrado intraoperatorio. La corrección preoperatoria de anemia y los umbrales restrictivos de transfusión mostraron beneficios adicionales. La evidencia sobre el uso del torniquete fue inconclusa. La evidencia que respalda el uso de cera ósea fue limitada. La evaluación mediante GRADE indicó una calidad alta de evidencia para TXA y anestesia regional, moderada para cirugía mínimamente invasiva, corrección de anemia y transfusión restrictiva, y baja para cera ósea. Conclusiones: Un enfoque multimodal que integre TXA, anestesia regional, cirugía mínimamente invasiva, corrección preoperatoria de anemia y protocolos restrictivos de transfusión reduce eficazmente el sangrado y las necesidades transfusionales en artroplastias bilaterales. Se recomienda su incorporación en protocolos ERAS (recuperación mejorada tras cirugía). Futuras investigaciones deberían refinar la dosificación del TXA, clarificar el uso del torniquete y evaluar la rentabilidad de estas intervenciones.